Secure Global Positioning System For Vehicle To Vehicle (V2V) Communication - et. al., Essa Ibrahim Essa, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we first focused on the developing a secure global positioning system for vehicle-to-vehicle (V2V) communication which adopts the secure transmission with respect to vehicle location. In literature, different existing positioning and wireless communication technologies have been presented with their detailed comparison with the global positioning system. In methodology we proposed a GPS-based model of Contention Intensity Control with Rate Control (CICRC) for efficient and secure V2V communication. We deduced the PDR and mean packet delay between heavy and low vehicle load scenarios under fully-connected vehicle network case and a hidden terminal participation case. We also presented the PDR and mean packet delay of safety messages generated with deterministic inter-arrival time and exponential inter-arrival time, respectively. Our GPS-based CICRC model provides a good match with simulation results on well-known MATLAB tool with wireless and networking toolbox. We also verified the model by showing our simulation provides good match with analytical results. Finally, comparing PDR, mean delay and PCR with proposed CICRC by some metrics, we can verify that CICRC improves V2V communication performance compared to existing communication methods. The simulation results we obtained show the packet delivery ratio under CICRC increases nearly 10% compared with that under CSMA [8] in heavy vehicle load scenarios for secure communication undermining the vehicle location. We have also found that if packet collisions occur in some vehicles at the during V2V communication, the collision probability between those vehicles in deterministic inter-arrival time will be always higher than that in exponential inter-arrival time. Average successful packet reception time under CICRC is around 20ms lower than CSMA in heavy vehicle loads, which verifies that CICRC improves on CSMA for the GPS performance especially in heavy vehicle load scenarios for secure communication